Tinjauan Yuridis Transaksi Jual Beli Akun Spotify di Indonesia - Bellia Argata Syahrani Bastari (Jurnal Hukum Lex Generalis, 2026)
The development of digital technology has encouraged the emergence of various forms of electronic transactions, including the practice of buying and selling digital music service accounts such as Spotify through unauthorized third parties. Although increasingly common, this practice lacks a clear legal basis and has the potential to cause legal losses for consumers and Spotify and violate the law. The research findings indicate that the sale and purchase transaction doesn’t comply with the contractual validity requirements as stipulated in Article 1320 of the Indonesian Civil Code and may potentially be an unlawful act. Strengthening regulations and increasing public legal awareness of the risks of illegal digital transactions are needed.